Developing Effective Marketing Strategies for A New Mro Company: A Case Study of Akasa Teknologi Nusantara At Soekarno-Hatta International Airport - Mahardhika Rizky G (Eduvest - Journal of Universal Studies, 2025)
The Maintenance, Repair, and Overhaul (MRO) industry plays a critical role in ensuring aircraft safety, operational efficiency, and compliance with regulatory standards. With the growing demand for air travel, the MRO sector in Indonesia is integral to maintaining fleet reliability and reducing downtime for safe aircraft operation. PT Akasa Teknologi Nusantara (ATN), a new entrant, plans to establish its MRO facility at Soekarno-Hatta International Airport, Indonesia's busiest aviation hub, where established players like Garuda Maintenance Facility (GMF) AeroAsia, FL Technics, and Batam Aero Technics dominate. To capture market share, ATN needs a well-structured marketing strategy to overcome industry challenges and capitalize on key opportunities. The research employs data triangulation with primary data collected through interviews with key stakeholders and statistical data from the Directorate General of Civil Aviation (DGCA). This study employs PESTEL analysis, Porter’s Five Forces, B2B Value Pyramid, VRIO analysis, STP (Segmentation, Targeting, and Positioning), and the 7P Marketing Mix to formulate a market entry strategy for ATN. The findings identify four critical differentiators for ATN: safety and compliance, quick turnaround times, operational efficiency, and service flexibility. By focusing on strategic partnerships, emphasizing these core values, and implementing an integrated marketing approach, ATN can establish itself as a credible alternative in the competitive MRO industry.